Effects of Dietary Ginsenoside Rg1 Supplementation on Growth Performance, Gut Health, and Serum Immunity in Broiler Chickens - Song, Zehe; Xie, Kaihuan; Zhang, Yunlu; Xie, Qian; He, Xi; Zhang, Haihan (Frontiers in Nutrition, 2021)
The restriction and banning of antibiotics in farm animal feed has led to a search for promising substitutes for antibiotics to promote growth and maintain health for livestock and poultry. Ginsenoside Rg1, which is one of the most effective bioactive components in ginseng, has been reported to have great potential to improve the anti-inflammatory and anti-oxidative status of animals. In this study, 360 Chinese indigenous broiler chickens with close initial body weight were divided into 5 groups. Each group contained 6 replicates and each replicate had 12 birds. The experimental groups were: the control group, fed with the basal diet; the antibiotic group, fed basal diet + 300 mg/kg 15% chlortetracycline; and three Rg1 supplementation groups, fed with basal diet + 100, 200, and 300 mg/kg ginsenoside Rg1, respectively. The growth performance, immune function, and intestinal health of birds were examined at early (day 1–28) and late (day 29–51) stages. Our results showed that dietary supplementation of 300 mg/kg ginsenoside Rg1 significantly improved the growth performance for broilers, particularly at the late stage, including an increase in final body weight and decrease of feed conversion ratio (P < 0.05). Additionally, the integrity of intestinal morphology (Villus height, Crypt depth, and Villus height/Crypt depth) and tight junction (ZO-1 and Occludin), and the secretion of sIgA in the intestine were enhanced by the supplementation of Rg1 in chicken diet (P < 0.05). The immune organ index showed that the weight of the thymus, spleen, and bursa was significantly increased at the early stage in ginsenoside Rg1 supplementation groups (P < 0.05). Our findings might demonstrate that ginsenoside Rg1 could serve as a promising antibiotic alternative to improve the growth performance and gut health for broiler chickens mainly through its amelioration of inflammatory and oxidative activities.